Complejo productivo y habitacional para campesinos afectados por la hidroeléctrica El Quimbo en la zona rural de Garzón-Huila. - Barragán Andrade, Andrés Felipe (Universidad Antonio Nariño, 2021)
This research work studies the cause and effect of the forced displacement of the resident and working peasant community that coexisted in the rural area of the municipalities of Garzón, Gigante and Agrado mainly, where more than 8,500 hectares were flooded in the central area of the department of Huila, of which 5,200 were areas of productive fertile land, due to the execution of the El Quimbo hydroelectric project, which makes use of the waters of the Suaza and Magdalena rivers. This generated social, environmental, and economic problems, affecting close to 300,000 people directly and indirectly, who lived from agricultural, fish and livestock production in this area. Ecosystems of riparian, dry and premontane forests disappeared, causing the loss of animal and plant species native to the region. The different structures of the area were analyzed, emphasizing the way this population lived before being displaced. For this purpose, several visits were made to the places where they are now settled, some formally living in the collective resettlements and others informally, living in the outskirts of the municipality of Garzón, where people who were not compensated in any way left, occupying private lots that are under threats and risks due to overflows, improvising inadequate housing for a dignified way of life. After the analysis carried out, it is concluded to design an urban sector proposal, which contemplates the way of living in the countryside in a collective and sustainable way, proposing the design based on the three main economic sectors (Primary "extraction of raw material", Secondary "transforming raw material into products" and Tertiary "provision of services") that meets the needs of the target population, articulated in the same space, where living and working complement each other, generating the recovery of the social fabric lost by the displaced peasants.